2013
DOI: 10.1177/0192623313501893
|View full text |Cite
|
Sign up to set email alerts
|

Subsite Awareness in Neuropathology Evaluation of National Toxicology Program (NTP) Studies

Abstract: This review manuscript is designed to serve as an introductory guide in neuroanatomy for toxicologic pathologists evaluating general toxicity studies. The manuscript provides an overview of approximately 50 neuroanatomical subsites and their functional significance across seven coronal sections of the brain. Also reviewed are three sections of the spinal cord, cranial and peripheral nerves (trigeminal and sciatic respectively), and intestinal autonomic ganglia. The review is limited to the evaluation of hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 121 publications
1
12
0
Order By: Relevance
“…These neuroanatomical areas represent important sites which comprise the population of neurons and glia cells vulnerable for neurodegerative conditions and or ageing processes in vertebrate animals. These also correspond to the neuroanatomical parts of the brain outline for neurologic studies in large animals (6,14,38,45). Changes observed in this study were consistent with changes reported by Gavier-Waden et al (15) who reported them as incidental findings in older cattle.…”
Section: Discussionsupporting
confidence: 91%
“…These neuroanatomical areas represent important sites which comprise the population of neurons and glia cells vulnerable for neurodegerative conditions and or ageing processes in vertebrate animals. These also correspond to the neuroanatomical parts of the brain outline for neurologic studies in large animals (6,14,38,45). Changes observed in this study were consistent with changes reported by Gavier-Waden et al (15) who reported them as incidental findings in older cattle.…”
Section: Discussionsupporting
confidence: 91%
“…The head of the animal was skinned, decapitated and immersion fixed for 24 hours in 10% NBF before brain removal. The brains were fixed for an additional five days before trimming into nine 5-mm coronal slices [ 51 , 52 ] using a brain-trimming matrix (Zivic). Tissues were processed in an automated Tissue-Tek VIP processor and paraffin-embedded with a Tissue-Tek TEC embedding station (Sakura Finetek USA, Torrance, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The sections were slide mounted and then stained with hematoxylin and eosin (H&E) or luxol fast blue counterstaineds with cresyl violet (LFB/CV). Specific neuroanatomic landmarks were identified and examined via light microscopy according to Rao et al 1,9 and Paxinos and Wason. 10 Paxinos and Watson's atlas was used in lieu of the Nomina Anatomica Veterinaria because the use of this atlas is integral to the neuroanatomic locations and calculations used by stereology and MRM.…”
Section: Methods: Neuropathologymentioning
confidence: 99%